Hybrid single‐port laparoscopic cisterna chyli ablation for the adjunct treatment of chylothorax disease in dogs. (30th March 2019) - Morris, Katherine P.; Singh, Ameet; Holt, David E.; Stefanovski, Darko; Singhal, Sunil; Bosco, Jessica; Capps, Michelle; McCallum, Michael; Runge, Jeffrey J.
Abstract: Objective: To describe a hybrid, single‐port, minimally invasive cisterna chyli ablation (CCA) technique in clinical cases of canine idiopathic chylothorax and evaluate this technique as a method for mesenteric lymphangiography (ML) in canine cadavers and clinical cases of idiopathic chylothorax. Study design: Cadaveric and retrospective study. Animals: Six canine cadavers and 14 client‐owned dogs with naturally occurring idiopathic chylothorax. Methods: Both cadaveric and clinically affected dogs were placed in sternal recumbency. A wound retractor device (WRD) and a single‐port device were placed in the abdominal flank 2–3 cm caudal to the 13th rib. Mesenteric lymphangiography was evaluated by using indocyanine green (ICG) in 6 canine cadavers. Single‐port laparoscopic CCA was performed in all clinical cases with idiopathic chylothorax. Results: Successful ML was completed by using ICG in all 6 canine cadavers. A right‐ or left‐sided single‐port laparoscopic CCA was successfully performed in 14 dogs with naturally occurring idiopathic chylothorax. Mesenteric lymphangiography was successfully performed through the WRD in 11 of these cases. No intraoperative complications were reported. Three dogs developed severe chyloabdomen postoperatively, with 1 dog requiring multiple abdominocenteses. Conclusion: Direct ML and single‐port laparoscopic CCA was performed through a WRD in dogs positioned in sternal recumbency. Although minimal operative complications were noted, postoperative chyloabdomen was reported. Clinical significance: This hybrid single‐port laparoscopic technique performed in sternal recumbency allows both a CCA and an intraoperative ML through the same incision. This procedure may be combined with thoracoscopic thoracic duct ligation and pericardectomy for the treatment of idiopathic chylothorax in dogs.